Agricultural credit survey, Nepal : the technical report, vol. 3 - Nepal Rastra Bank. (Kathmandu : Nepal Rastra Bank, Research Dept, 1972)
This is a report of agricultural credit survey undertaken by the Nepal Rastra Bank.
oo 14/01/2019
Ref
Keywords: Agricultural credit; Agricultural finance; Nepal